Didogobius janetarum sp. nov., a new cryptobenthic goby species from the Cape Verde Islands (Teleostei: Gobiidae) - Schliewen, Ulrich K.; Wirtz, Peter; Kovačić, Marcelo (Zootaxa, 2018)
Didogobius janetarum sp. nov. is described from five specimens collected from small caves and rock crevices between 12 and 20 m depth off two locations of Santiago Island, Cape Verde Islands. The species differs from all currently described congeners by the combination of the following characters: (1) 27 vertebrae, (2) second dorsal fin I + 10, (3) posterior quarter of predorsal region in front of first dorsal fin origin scaled, with several rows of cycloid scales, (4) body squamation cycloid anteriorly and ctenoid posteriorly, (5) scales in the lateral series 30–32, (6) anterior oculoscapular canal present, (7) preopercular head canal absent, (8) suborbital row 7 each a single papilla, (9) suborbital rows 2 and 4 close to orbit, and by (10) branchiostegal membranes uniformely black below preopercle, forming a V-shaped mark. Definitions for all used meristic counts are presented to serve as a reference for gobioid meristic studies. The genus is rediagnosed to accommodate recently described Didogobius species.